Geochemical Characteristics of Crude Oil in Member 7 of Yanchang Formation in Yanchang Oilfield - Wenming Li; Zhendong Gao; Yongdong Wang; Jingyang Pu; Hanlie Cheng; Fahim Theon (Journal of Chemistry)
Oil is an important primary energy for national production and life and national defense, and China is the key to rapid development. It is of great strategic significance to ensure the safe and efficient production of the oil industry. Yanchang Oilfield is located in the main position of oil and gas accumulation in Ordos Basin, China, and the seventh member of the Yanchang Formation is the area with the richest crude oil output at present. Studying the geochemical characteristics of its crude oil exploitation is of great engineering significance for the exploration of oil and gas content in similar terrain and the continuous improvement of oil extraction and refining technology. On the other hand, it also provides first-hand data and important technical references for the exploration and exploitation of oil and gas resources in other areas of the Ordos Basin. Firstly, this paper points out the important strategic significance of the petroleum industry for China’s development, and briefly describes the basic situation of Yanchang Oilfield and the basic characteristics of crude oil. The power and diversion system of the Yanchang Formation in Yanchang Oilfield are studied, and the main factors of formation and flow of deep reservoirs in the Yanchang Formation are explored, as well as the regional geological survey of the Yanchang Formation No. 7 in Yanchang Oilfield. The characteristics of crude oil and its maturity evaluation system are emphatically discussed, and the changes in crude oil characteristics under the action of microorganisms are comparatively studied. In this paper, Yanchang Oilfield, the main reservoir area of the Ordos Basin, is taken as the research object, and the formation mechanism of the oil reservoir and the geochemical characteristics of crude oil in the 7th member of the Yanchang Formation are deeply explored, so as to provide a preliminary theoretical study for the research of crude oil exploitation in reservoirs and other oilfields in the Ordos Basin.